Why the future is ours to mold: an interview with Alec Antoine by Saori Shinjiro / Enabella Tasha Dennis ... [et al.] - Dennis, Enabella Tasha; Juman, Juliet Cheria; Abdul Khalik, Khairunisa; Nyareng, Rasiba (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
A news article can include accounts of eyewitnesses to the happening event. It can contain photographs, accounts, statistics, graphs, recollections, interviews, polls, debates on the topic, etc. Headlines can be used to focus the reader’s attention on a particular (or main) part of the article. The writer can also give facts and detailed information following answers to general questions like who, what, when, where, why and how.